Lycopene Ameliorates Experimental Colitis in Rats via Reducing Apoptosis and Oxidative Stress - Baykalir, Burcu Gul; Aksit, Dilek; Dogru, Mustafa Selim; Yay, Arzu Hanim; Aksit, Hasan; Seyrek, Kamil; Atessahin, Ahmet (Verlag Hans Huber, 2016)
Inflammatory bowel disease (IBD) is an inflammatory disorder involving colitis. Lycopene is a naturally occurring carotenoid that has attracted considerable attention as a potential chemopreventive agent. The impact of lycopene on colitis is currently unknown. The aim of this study was to investigate the protective effects of lycopene in a rat model of colitis induced by acetic acid. The animals were randomly divided into the following five groups: the control group, colitis group, colitis + sulfasalazine group as a positive control group, colitis + lycopene and lycopene groups. Colonic mucosal injury was assessed by biochemical and histopathological examinations. Malondialdehyde (MDA), superoxide dismutase (SOD) activity, total antioxidant status (TAS), ceruloplasmin (CPN), total sialic acid and iron (Fe) levels were evaluated in blood samples. MDA, SOD, TAS and DNA fragmentation levels were also measured in colon tissues. MDA (p < 0.05), total sialic acid (p < 0.05) and DNA fragmentation levels (p < 0.01) were significantly higher, and the activity of the antioxidant enzyme were lower in the colitis group than in the control group. Treatments with lycopene in the colitis decreased MDA, total sialic acid and DNA fragmentation levels, while SOD activity (p < 0.05), TAS (in colon p < 0.05; in serum p < 0.01), CPN (p < 0.05) and Fe levels (p < 0.05) were significantly increased. The histopathological evaluation also confirmed the foregoing findings. Treatment with lycopene ameliorated the biochemical and pathological alterations caused by colitis. The results obtained in this study indicate that lycopene may exert protective effects in experimental colitis and might, therefore, be useful for treatment of IBD.
Keywords: Colitis; lycopene; oxidative stress; immunohistochemistry; apoptosis